Redescription of the poorly known ghost shrimp species, Scallasis amboinae Bate, 1888, review of the genus, and description of a new species from the Ryukyu Islands, Japan (Decapoda: Axiidea: Callianassidae) - Komai, Tomoyuki; Poore, Gary C. B.; Fujita, Yoshihisa (Zootaxa, 2020)
A poorly known callianassid ghost shrimp species, Scallasis amboinae Bate, 1888, is redescribed and illustrated on the basis of the holotype and new material from Papua New Guinea. A new species, S. inermis, is described from the Ryukyu Islands, Japan. Callianassa (Cheramus) pygmaea De Man 1928 is synonymised with S. amboinae. All seven species of Scallasis are diagnosed and compared.